Une activité touristique et de loisir « amphibie » entre espaces de pratiques et territoires de gestion : la plaisance - Ewan Sonnic (Confins)
In the era of mass tourism and leisure, pleasure sailing is a particular expression of territoriality through various equipment on the coast (ports, marinas, shipyards, etc.) and of maritime as terrestrial flows (routes followed at sea by the yachtsmen between ports, connections between residence and loading points, shuttles between residence and work for professionals of pleasure, sailing, etc.). This “amphibious” character confers on the pleasure sailing an atypical place among the tourist activities.In France, more than for other leisure, the pleasure sailing is quartered between reference spaces, (resulting essentially from the trajectories of the yachtsmen, navigation basins, cruising basins, pleasure sailing basins…), and of administrative territories concerned with a quite different logic on the ground (territorial collectivities, subdivisions of the maritime businesses) and at sea (territorial water, zone of exercise of police rights).Like many other “lived” spaces, the surfaces for practice of pleasure sailing are particularly complex. In addition to their chronic character, taking into account the primarily seasonal character of the activity, these territories will depend on the diversity of the practices (fishing, strolls at sea, coastal cruising, deep-sea cruising, sporting sailing), of the unconscious or conscious limits that each yachtsman fixes, of the physical determinism (obstacles to navigation, winds, currents…), of the current regulations which prohibits navigation beyond certain distance from a shelter according to the various categories of ships, etc. As for the management territories, they stem from a mainly continental logic, even on the seacoast. The lack of coincidence between practice spaces and management spaces is such as to lead several actors (territorial collectivities, decentralized services of the State, research departments, associations…) to operate more and more within the framework of territories copied on practice spaces. The latter remain nevertheless largely fixed by traditional administrative cuttings and see their regularly redefined.